Circuit Game Development: Effects on Balance, Concentration, Muscle Endurance, and Arrow Accuracy - Betrix Teofa Perkasa Wibafied Billy Yachsie; Suharjana; Ali Satia Graha; Amri Hartanto (OVS LLC, 2023)
Study purpose. Balance, concentration, muscle endurance, and accuracy are very important for archery athletes, but there are still limited game models to improve balance, concentration, arm muscle endurance, and accuracy in archery athletes.  The aim of this research is to develop a circuit game model to improve balance, concentration, arm muscle endurance, and accuracy in proper and effective archery athletes. Materials and methods. The development model used in this study is based on Lee & Owens theory which uses five phases in a cycle, namely ADDIE. The effectiveness test was carried out on archery athletes aged 10-13 years, totaling 30 people. Treatment was given for 18 meetings. Results. The conclusion of the research is that the circuit game model to improve balance, concentration, arm muscle endurance, and accuracy in archery athletes is feasible. The circuit game model is effective in improving balance, concentration, arm muscle endurance, and accuracy in archery athletes. The circuit game model consists of 6 posts. Conclusions. For coaches, the circuit game model can be used to improve balance, concentration, arm muscle endurance, and accuracy in archery athletes. Suggestions for further researchers are that this circuit game model needs to be developed again to be better.